Circular RNA circDCUN1D4 suppresses hepatocellular carcinoma development via targeting the miR-590-5p/ TIMP3 axis - Hongyu Li; Bing Su; Yan Jiang; Boyang Zhang; Rulong Du; Can Song; Bin Hou; Kun Xu; Lida Wu; Yuchun Gu (Molecular Cancer)
Abstract Hepatocellular carcinoma (HCC) is a major global health concern, necessitating innovative therapeutic strategies. In this study, we investigated the functional role of circular RNA circDCUN1D4 in HCC progression and its potential therapeutic implications. It was found that HCC patients exhibiting higher levels of circDCUN1D4 demonstrated a more favorable survival rate. Furthermore, we revealed that circDCUN1D4 suppressed HCC cell proliferation, migration, and invasion. Mechanistically, circDCUN1D4 was identified as a sponge for miR-590-5p, leading to the downregulation of its downstream target, Tissue Inhibitor of Metalloproteinase 3 (TIMP3). Importantly, circDCUN1D4 administration through In vivo jet-PEI exhibited a robust inhibitory effect on tumor progression without causing notable toxicity in mice. Overall, our findings highlight circDCUN1D4 as a promising therapeutic candidate for HCC, unraveling its intricate regulatory role through the miR-590-5p/TIMP3 axis. This study contributes valuable insights into the potential clinical applications of circRNA-based therapies for HCC.